Variation of milk technological properties in sheep milk: Relationships among composition, coagulation and cheese-making traits. (October 2019) - Vacca, G.M.; Cipolat-Gotet, C.; Paschino, P.; Casu, S.; Usai, M.G.; Bittante, G.; Pazzola, M.
Abstract: The relationships between milk composition, coagulation properties and cheese-making traits in sheep milk were characterised. Ten traits related to milk coagulation (RCTeq, kCF, CFp ), cheese yield (%CYCURD, %CYSOLIDS, %CYWATER ), and curd nutrients recovery or whey loss (%RECFAT, %RECPROTEIN, %RECSOLIDS, %RECENERGY ) were recorded. To obtain a measure of the efficiency in terms of %CY, the ratio between the observed and the theoretical %CY ( Ef -%CYCURD, Ef -%CYSOLIDS ) was calculated. Sheep milk showed good qualities for coagulation and cheese production; milk lactose appeared to be the component most linked to gelation, curd firming time and water retained in the curd. In the case of milk protein, an opposite relationship with gelation time was observed. Milk fat and protein positively affected total solids recovery and yield inducing higher %CYCURD . Relationships with CFt parameters were limited; curd firming instant rate seems to be the most informative trait to assess the efficiency of the cheese-making process.